Transforming Nursing, 22-24 May 2014, Riverside Majestic Hotel, Kuching Sarawak - Universiti Malaysia, Sarawak (Universiti Malaysia Sarawak, UNIMAS, 2014)
Conference programme and abstracts book. Organised by the Nursing Council of the Public Institutions of Higher Learning Malaysia, Universiti Malaysia Sarawak, Universiti Sains Malaysia ; supported by Kementerian Pendidikan Malaysia and Sarawak Convention Bureau ; Hosted by Universiti Malaysia Sarawak.